1987
DOI: 10.1016/0885-2308(87)90014-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of natural and synthetic speech: effects of predictability on the verification of sentences controlled for intelligibility

Abstract: A sentence verification task (SVT) was used to study the effects of sentence predictability on comprehension of natural speech and synthetic speech that was controlled for intelligibility. Sentences generated using synthetic speech were matched on intelligibility with natural speech using results obtained from a separate sentence transcription task. In the main experiment, the sentence verification task included both true and false sentences that varied in predictability. Results showed differences in verifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…But these perceptual capabilities have limits, and cognitive effort increases and accuracy decreases as the acoustic information becomes degraded or unreliable ͑Munro and Derwing, 1995;Pisoni et al, 1987͒. This is precisely the case with the perception of dysarthric speech.…”
Section: Introductionmentioning
confidence: 97%
“…But these perceptual capabilities have limits, and cognitive effort increases and accuracy decreases as the acoustic information becomes degraded or unreliable ͑Munro and Derwing, 1995;Pisoni et al, 1987͒. This is precisely the case with the perception of dysarthric speech.…”
Section: Introductionmentioning
confidence: 97%
“…shown in figure 43.3 indicated that subjects were consistently faster in responding, to natural speech than to synthetic speech. For both natural and synthetic speec~;: responses were faster for high-predictability sentences than for low-predictabjIi,tY:':; sentences [PMD87]. The results showed that although the sentences were intelligible, even high-quality synthetic speech is not perceived in the same as natural speech.…”
Section: Comprehension Of Synthetic Speechmentioning
confidence: 67%
“…Although some have found rule-based synthetic speech to attain performance levels approximating those of natural and digitized speech, results from other studies have indicated inferior comprehension performance (Moody and Joost, 1986;Pisoni and Hunnicutt, 1980;Pisoni, Manous, and Dedina, 1987;Schwab, Nusbaum and Pisoni, 1985). This difference in comprehension performance between synthetic and natural speech may be mediated by the amount of familiarization, which several researchers have found to enhance the intelligibility and comprehension performance of synthetic speech, at times approaching levels comparable to natural speech (Herlong and Williges, 1988;Pisoni and Hunnicutt, 1980;Stecyk-Ramos, Maddox and Strybel, 1988).…”
Section: Speech Characteristicsmentioning
confidence: 95%
“…A total of 64 sentences were selected from a study performed by Pisoni, Manous, and Dedina (1987). In that study, a group of 40 introductory psychology students was asked to create true and false sentences by providing the final word to complete a series of sentence frames.…”
Section: Apparatusmentioning
confidence: 99%